Turbulence model choice for the calculation of drag forces when using the CFD method - Zaidi, H.; Fohanno, S.; Taiar, R.; Polidori, G. (Journal of Biomechanics, 2010)
The aim of this work is to specify which model of turbulence is the most adapted in order to predict the drag forces that a swimmer encounters during his movement in the fluid environment. For this, a Computational Fluid Dynamics (CFD) analysis has been undertaken with a commercial CFD code (Fluent®). The problem was modelled as 3D and in steady hydrodynamic state. The 3D geometry of the swimmer was created by means of a complete laser scanning of the swimmer`s body contour. Two turbulence models were tested, namely the standard k-e model with a specific treatment of the fluid flow area near the swimmer`s body contour, and the standard k-w model. The comparison of numerical results with experimental measurements of drag forces shows that the standard k-w model accurately predicts the drag forces while the standard k-e model underestimates their values. The standard k-w model also enabled to capture the vortex structures developing at the swimmer`s back and buttocks in underwater swimming; the same vortices had been visualized by flow visualization experiments carried out at the INSEP (National Institute for Sport and Physical Education in Paris) with the French national swimming team.